Differences in physical and mental health symptoms among residents living near municipal solid waste sites: a cross sectional study in the Ashanti Region, Ghana - Prince Peprah; Williams Agyemang-Duah; Anthony Kwame Morgan; Ellen Onyina; Evelyn Serwaa Asare (Journal of Health, Population and Nutrition, 2024)
Abstract Objective Physical and mental health concerns and symptoms, including sleep problems, low mood, extreme tiredness, and appetite loss are prevalent among people living near waste sites. This research examines differences in health symptoms among residents living near municipal solid waste sites in the Ashanti Region, Ghana. Methods The study used cross-sectional data from 827 residents living near three municipal waste sites, including Besease, Asokore, and Dompoase sites in the Ashanti Region, Ghana. Descriptive statistics, Pearson’s chi-square, and binary logistic regressions were performed to examine the differences and associations between the variables. Results Health symptoms, including sleep problems/insomnia, frequent extreme tiredness, low mood, loss of appetite, stress, anxiety, and depression, were reported by the majority of the participants. Residents near open dumpsites (Besease and Asokore) exhibit significantly higher likelihoods of experiencing various health symptoms such as extreme fatigue, depression, psychological disorders, thinking and concentration problems, low mood, loss of appetite, and anxiety compared to those near the engineered Oti landfill in Dompoase. Conclusion While emphasizing the importance of proper landfill design and management in Ghana, this study underscores the need for further longitudinal and clinical investigations. Clinically establishing the link between dumpsites and health symptoms is imperative for informed public health interventions and policy decisions aimed at mitigating the potential adverse health effects of landfills on residents' well-being.